Multiple sclerosis in the Iranian immigrant population of BC, Canada: prevalence and risk factors. (August 2014) - Guimond, Colleen; Lee, Joshua D; Ramagopalan, Sreeram V; Dyment, David A; Hanwell, Heather; Giovannoni, Gavin; Criscuoli, Maria; Yee, Irene M; Vorobeychik, Galina; Ebers, George C; Sadovnick, A Dessa
Background: There is a well-documented increase in the risk of multiple sclerosis (MS) when migrating from a region of low prevalence to one of high prevalence. Objective: We present here an investigation of MS prevalence and candidate environmental and genetic risk factors among Iranian immigrants to British Columbia (BC), Canada. Methods: MS cases of Iranian ancestry were ascertained from a population-based Canadian study. We collected blood samples for genetic and serological analyses, and administered a personal history questionnaire to the cases. Results: The crude prevalence of MS in this population of Iranian ancestry was 287/100, 000 (95% CI: 229 – 356/100, 000). MS cases were more likely to have a history of infectious mononucleosis (odds ratio (OR) = 7.5; p = 0.005) and smoking (OR = 17.0; p < 0.0001), as compared to healthy controls from previous studies in Iran. Cases were also more likely than controls to have been born between April and September (OR = 2.1; p = 0.019). Conclusion: The prevalence of MS among Iranian immigrants to Canada is greater than the overall prevalence of MS in Iran by a factor of at least four, and is similar to that recently observed among Iranian immigrants in other western nations. No major genetic susceptibility variants were identified, suggesting the environment in Canada may be what is increasing the risk of MS in this population.